ANALYSIS OF LOGISTIC EFFICIENCY: ANALYSIS OF LOGISTIC EFFICIENCY - Kazakov, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Improving the efficiency of logistics is the basis of economic growth and business competitiveness. Politicians around the world recognize that the logistics sector is one of their main pillars of development. Countries that are a source of trade influence in Europe, such as the Netherlands, as well as developing countries such as Vietnam or Indonesia, see seamless and sustainable logistics as a driver of growth and integration with global value chains.